The implications of remittances for agricultural land use and fuelwood collection: evidence from the remaining forested landscapes in the Philippines. (1st February 2022) - Zhunusova, Eliza; Lippe, Melvin; Yang, Anastasia Lucy; Günter, Sven
Abstract: Despite the projected sharpest decline in remittances in history due to the global economic crisis induced by the COVID-19 pandemic, remittances are expected to remain an important source of external financing for many developing countries. The Philippines is among the top five recipients of remittances worldwide, while outmigration is an important livelihood strategy for rural communities in the country due to rapid population growth, poor employment opportunities, and scarce agricultural land. Migration and remittances can influence smallholder land use with potential implications for forest resource use through an impact on household income and household decisions on local activities. However, little attention has been paid in previous research to how remittances relate to changes in rural households' land use and their implications for forests. The goal of this study is to investigate the links between the inflow of both international and internal remittances and rural households' land use in forested landscapes in the Philippines. In order to do that, we use the data from 1024 household surveys and an instrumental variable approach to investigate the impact of remittances on fuelwood use and on the area cultivated by perennials and cereals. The findings of this study show that remittances positively influence the size of land planted by perennials and reduce households' reliance on fuelwood use. Our findings provide an improved understanding of the links between migration—remittances—natural resource management, which will become especially relevant as countries struggle to deal with the economic fallout associated with COVID-19. We argue that demographic policy measures should play a bigger role in land use, land use change, and forestry negotiations than before. Moreover, global sustainability agendas such as the sustainable development goals should recognize the impacts of migration on natural resources to help bridge the gap between developmental and environmental goals.